Acquisition and Online Display of High‐Resolution Backscattered Electron and X‐Ray Maps of Meteorite Sections - Ryan C. Ogliore (Earth and Space Science, 2021)
Abstract Analyses of meteorites in thin or thick section begins with a detailed mineralogic/petrologic study of the sample. Backscattered electron and X‐ray imaging in a scanning electron microscope is critical for the characterization and study of the meteorite sections at sub‐μm to cm size scales. Here, I describe techniques to acquire backscattered electron and X‐ray images of an entire one‐inch thin or thick section at high resolution, assemble large mosaic mosaic maps of the data, and display the maps conveniently online in a web browser. The code to acquire, stitch, and display the maps is made available as an open‐source project on GitHub.